Legislation Performance Approach Through The Formulation of Regional Policy in East Nusa Tenggara - Manubulu, Isakh Benyamin; Sudwika Utama, I Putu Raditya; Alam, Sajid Munandar (Literasi Hukum, 2023)
The policy of Victor Laiskodat as the Governor of East Nusa Tenggara has highlight public attention since the obligation to start learning hours at 05.00 WITA (Central Indonesia Time) because the government has improved the allocation of education funds on East Nusa Tenggara Province is 34% of the Regional Revenue and Expenditure Budget. Besides that, the policy of the Regent of North Central Timor prohibits smoking and eating betel nut as well as requiring the demolition for smoking and eating betel nut facility. Those policy then bring up an issue about conception regulation policy as well as performance of legislation in East Nusa Tenggara. This research has formulated with normative study, supported by legislation approach, analysis and conceptual approach, and the facts approach, then the author finds the final results and recommendations that the policy does not meet the criteria intended in a policy regulation and even resulting conflicting norms while legislative performance in East Nusa Tenggara Province is still needs to be improved, especially in the aspect of understanding basic legal concepts and policy